Adult Psychology of Religion in Relation to Religious Counseling Programs and Strategies - Ardimen, Ardimen; Maswar, Rezi; Langputeh, Sukree (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2024)
This research analyzes the relationship between religious psychology and religious counseling through a systematic literature review method. In this review, researchers want to identify the psychology of adult religion, the religious characteristics of adults, the development of religion in adults and the relationship between the psychology of religion and religious counseling. In each of these aspects, relevant literature is studied. The results of this literature review can provide insight into the psychology of religion in adult religious counseling, assist counselors and researchers in developing counseling approaches and guide the future development of the counseling field.